2013
DOI: 10.1177/1059840512472708
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Teen Mentors to Adult Teachers on Child Lifestyle Behaviors and Health Outcomes in Appalachia

Abstract: Childhood obesity prevalence rates in the United States are the highest in the rural Appalachian areas. Teens mentoring younger children to reverse obesity health risks are an understudied approach. This randomized-controlled trial compared the effects of two curriculum delivery methods and assessed the mediating effects of the number of sessions attended on the outcomes. The control group received the 8-week Just for Kids! curriculum via an adult teacher in a classroom and the experimental group received the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 30 publications
(45 reference statements)
1
63
0
Order By: Relevance
“…Peer mentors provide personal support and guidance to these overcoming environmental, social, and psychological barriers, leading to improved adherence to physical activity and increased peer resources to sustain physical activity. Serving as role models, peer mentors improve their own lifestyle behaviors, providing a dual effect of the intervention (SAMHSA, 2014; Smith & Holloman, 2013). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer mentors provide personal support and guidance to these overcoming environmental, social, and psychological barriers, leading to improved adherence to physical activity and increased peer resources to sustain physical activity. Serving as role models, peer mentors improve their own lifestyle behaviors, providing a dual effect of the intervention (SAMHSA, 2014; Smith & Holloman, 2013). …”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of trained peer mentors lead to physical activity behavior change and better health outcomes in mentees, compared to the same curriculum being delivered to classroom teachers (Smith, 2011; Smith & Holloman, 2013). Mentored groups achieved improved blood pressure and body mass index outcomes, compared to teacher-led groups (Smith, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…6 The inclusion of a mentoring component has resulted in direct improvements for children in skill development, 6 selfefficacy, 7,8 sense of self-worth, 9 and health outcomes. 7,8 School-based mentoring programs benefit not only the teenager and peer mentor but also the school and communities by establishing social networks that integrate positive role models as mentors from the same community into the school, 10 thus enhancing connectedness to one's school and community. It has been suggested that school connectedness is the single most effective aspect of the school environment in predicting healthier behaviors and better health.…”
mentioning
confidence: 99%
“…[ [34][35][36] Although mentoring had a positive effect on healthy eating self-efficacy and one-week eating habits, there was little difference in behavior and knowledge outcomes in this group when compared with the adult-led group. Further research utilizing mentors in the promotion of health among school age children are needed to determine if the amount of time mentors and participants spend in intervention programs impact health behaviors of participants.…”
Section: Discussionmentioning
confidence: 99%